2012
DOI: 10.5539/ijps.v4n2p141
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Subjective Age and Adjustment to Aging in a Portuguese and German Older Population: A Comparative Multiple Correspondence Analysis

Abstract: Purpose: This study aims at examining the contributors to adjustment to aging (AtA) and subjective age (SA) identified by older adults and to investigate the latent constructs that can work as major determinants in AtA and SA in an older Portuguese and German population.Method: Measures were completed, using a variety of appropriate methods, including demographics and interviews. Complete data were available for 102 older adults aged between 74-100 years (M=81.2; SD = 6.70). Data was subjected to content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The finding that aging identity was directly influenced by stressors in the family and work domains, though not by rewards, is in line with other studies. Other studies have reported that strain in interpersonal relationships (Cha, Seo, & Sok, 2012; von Humboldt, Leal, & Pimenta, 2012), such as family relationships, are viewed as social losses, whereas work strain may be viewed as losses in personal achievement or financial control (Furstenberg, 2002). Losses make individuals perceive their aging more negatively (Holahan & Velasquez, 2011; Knight & Ricciardelli, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that aging identity was directly influenced by stressors in the family and work domains, though not by rewards, is in line with other studies. Other studies have reported that strain in interpersonal relationships (Cha, Seo, & Sok, 2012; von Humboldt, Leal, & Pimenta, 2012), such as family relationships, are viewed as social losses, whereas work strain may be viewed as losses in personal achievement or financial control (Furstenberg, 2002). Losses make individuals perceive their aging more negatively (Holahan & Velasquez, 2011; Knight & Ricciardelli, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The present study, as well as the studies by von Humboldt, Leal, and Pimenta (2012a,b), constitute part of a multiphase project entitled, “Older adults' adjustment to aging and subjective well‐being,” for which support was given by the Portuguese Foundation for Science and Technology (FCT) and ethical approval was given by the Superior Institute of Applied Psychology‐University. Informed consent was received from all participants and the study protocol was approved by the Research Unit in Psychology and Health.…”
Section: Methodsmentioning
confidence: 99%
“…In general, previous scholars have used MCA in marketing research (Kaciak and Louviere, 1990), the usage of medical care and medicine (Bonnefoy-Mazure et al, 2013;Liu and Liu, 2011), geology and geography applications (Dai and Lee, 2001), psychological analysis (von Humboldt et al, 2012), and tourism behaviorrelated studies (Richards and van der Ark, 2013). However, the use of MCA in patent analysis is insufficient.…”
Section: Patent Portfolio Positioning Analysismentioning
confidence: 99%